DNA and biotechnology - Fitzgerald-Hayes, Molly (Academic Press/Elsevier, 2010)
Appropriate for a wide range of disciplines, from biology to non-biology, law and nursing majors, DNA and Biotechnology uses a straightforward and comprehensive writing style that gives the educated layperson a survey of DNA by presenting a brief history of genetics, a clear outline of techniques that are in use, and highlights of breakthroughs in hot topic scientific discoveries. Engaging and straightforward scientific writing style Comprehensive forensics chapter Parallel Pedagogic material designed to help both readers and teachers. Highlights in the latest scientific discoveries Outstanding.
Keywords: DNA.; Biotechnology -- Research.; elektronické knihy; electronic books